A case of rhupus-reporting of a rare entity - Preema Sinha; Anuj Singhal; Saikat Bhattacharjee; Bhavni Oberoi (Wolters Kluwer Medknow Publications, 2019)
Rhupus syndrome, a rare entity, is the co-existence of systemic lupus erythematosus (SLE) with rheumatoid arthritis (RA). It manifests as more RA and less SLE related damages. The duration of the disease is longer than typical RA or SLE. Controversies exist regarding the definition of Rhupus. The incidence of Rhupus in patients with arthritis is 0.01%-0.2% and <2% in patients with connective tissue diseases. However, we report a rare case of rhupus in a 55-year-old lady with polyarthritis and joint deformities of 6 year duration, presenting with features of lupus erythematosus.